P57. Safety and tolerability of spermidine supplementation: A translational study in mice and older adults with subjective cognitive decline. Issue 8 (August 2018) - Schwarz, C.; Wirth, M.; Benson, G.; Köbe, T.; Stekovic, S.; Madeo, F.; Flöel, A.
Abstract : Background: Supplementation of spermidine, an autophagy-inducing agent, has been shown to protect against neurodegeneration and memory impairment in aged animal models. We report a translational study aiming to determine safety and tolerability of a wheat germ extract containing enhanced spermidine concentrations in murine model and a human cohort of older adults with subjective cognitive decline (SCD), a risk factor of dementia. Methods: In murine model, safety of various dosing strategies was assessed using a sub-chronic, oral administration scenario. Post mortem examination of mice included macroscopic inspection of organs, organ weighing and neoplastic examination after 28 days of spermidine supplementation at various concentrations. In addition, animal behavior and animal bodyweight were controlled during the treatment to detect any negative effects. In the human cohort, a randomized, placebo-controlled, double-blind Phase II study was carried out over 3 months to assess safety and tolerability of spermidine supplementation. Safety assessments included vital signs, weight, clinical chemistry and hematological parameters of safety, as well as self-reported health status at the end of intervention. Frequency, duration and severity of adverse event was monitored throughout the trial. Results: In the preclinical toxicity study, spermidine supplementation did not result in morbidities or changes in behavior in BALBc/Rj mice during the 28-days repeated-dose tolerance study. Post mortem examination of the mice organs showed no significant increase in tumorigenic and fibrotic events. In the human cohort, no differences were observed between spermidine and placebo-treated groups in vital signs, weight, clinical chemistry and hematological parameters of safety, as well as in self-reported health status at the end of intervention. Compliance rates were above 85% and indicated excellent tolerability. Conclusion: Findings of this translational study demonstrate that spermidine supplementation using a spermidine-rich plant extract is safe and well-tolerated in mice and older adults. These findings call for longer-term intervention studies in humans to investigate the impact of spermidine treatment on memory function and brain integrity.